Stereoselective Synthesis of Acyclic Skeleton of Boscartin A - Saha, Dhiman; Sahana, Moinul Haque; Mandal, Gour Hari; Goswami, Rajib Kumar (Synlett, 2022)
Stereoselective synthesis of key acyclic skeleton of structurally challenging and biologically active boscartin A possessing six stereogenic centers, among which three are tertiary, has been achieved for the first time. The synthetic study comprises the Sharpless asymmetric epoxidation (SAE) followed by stereoselective epoxide opening for installation of C-11 and C-12 centers, Meyer–Schuster rearrangement followed by intramolecular oxa-Michael addition for construction of C-1 center, SAE followed by CBS reduction and subsequent cycloetherification for stereoselective generation of C-3, C-4, and C-7 centers, Gilman reaction for introduction of C-9 olefin and Grignard reaction for installation of C-8 olefin.
Keywords: stereoselective synthesis; Sharpless asymmetric epoxidation; boscartin A